The "Crumple Zone" hypothesis: Association of frontal sinus volume and cerebral injury after craniofacial trauma. Issue 7 (July 2017) - Cai, Stephen S.; Mossop, Corey; Diaconu, Silviu C.; Hersh, David S.; AlFadil, Sara; Rasko, Yvonne M.; Christy, Michael R.; Granta, Michael P.; Nam, Arthur J.
Abstract: Purpose: The paranasal sinuses are complex anatomical structures of unknown significance. One hypothesis theorizes that the sinuses, in the event of a traumatic injury, function as a crumple zone to distribute and absorb energy to protect the brain and other critical structures. The current study investigates the association between frontal sinus (FS) volume and the severity of cerebral insults following craniofacial trauma. Methods: All patients with FS fracture admitted to a level 1 trauma center from 2011 to 2014 were retrospectively reviewed. FS volumes were measured from computed tomography (CT) on admission using a proprietary region growing segmentation tool. Head injuries were classified based on the presence of specific types of intracranial pathology and their corresponding Marshall Score. Results: FS fracture was identified on the admission CT in 165 patients. Male patients had significantly larger FS volume compared to females (8.4 ± 6.3 vs. 4.0 ± 2.9 cm 3, p  < 0.001). Smaller FS volume was significantly associated with a worse Marshall Score ( p  = 0.041) and a higher incidence of cerebral contusion ( p  = 0.016) independent of age, gender, mechanism, ISS, and admission GCS. The inverse correlation between FS volume and the Marshall Score was also statistically significant (Spearman correlation coefficient r  = −0.19, p  = 0.015). Smaller FS volume was observed in patients who suffered intracranial insults, underwent neurosurgical interventions, and had worse clinical outcomes and trended towards significance with respect to an association with subarachnoid hemorrhage ( p  = 0.074) and subdural hematoma ( p  = 0.080), and had a statistically significant association with longer length of stay ( p  < 0.001). Conclusion: FS volume is inversely correlated with the severity of intracranial pathology following craniofacial trauma. Our findings are consistent with the "crumple zone" hypothesis and suggest that the FS likely plays a role in mitigating intracranial injury. Furthermore, FS volume is significantly different between male and female patients. This is a novel finding that warrants further validation.